Electronic feedback or handwritten feedback: What do undergraduate students prefer and why? - Bruce Spitzer; Frank X. McGoron; Emily E. Williams; Michelle A. Bakerson; A. Bruce Watson; Ni Chang (Journal of Teaching and Learning with Technology, 2012)
Giving feedback on students’ assignment is, by no means, new to faculty. Yet, when it comes to handwritten feedback delivered in person and typed feedback delivered electronically to students, faculty may not know what undergraduate students prefer and reasons behind their preferences. The present study explored which form of feedback, i.e., electronic or handwritten feedback, undergraduate students preferred and rationale behind their preferences. Two hundred fifty respondents completed an online survey, which consisted of three closed-ended questions and two open-ended questions. Nonparametric tests were used to analyze the quantitative data. Qualitative responses were read and analyzed by four researchers and six themes were identified. The qualitative data were rechecked against the six themes independently first and then collectively. Discrepancies were discussed before complete consensus was made. The study found that nearly 70% of the participants preferred e-feedback for its accessibility, timeliness, and legibility. Yet, with respect to the quality of feedback, the majority of handwritten supporters chose handwritten feedback, as they perceived this type of feedback as more personal. The article discusses the marked discrepancies between the two groups and ends with educational implications and suggestions for future research.